Economic Order Quantity to Control Raw the Materials Inventory on “Zaskya Bakery” Home Industry - Lukman Hidayat; Hidayat Koto; Hayyuning Pratiwi (BPFP Faperta UNIB, 2020)
Zaskya Bakery Home Industry is one of the small industries that produce various types of sweet bread in Central Bengkulu Regency. Optimal raw material inventory control is essential for companies to make the production process good. The economic order quantity (EOQ) method is the basic method of inventory control by finding the minimum point between ordering costs and storage costs. The purpose of this study was to determine the inventory control of some raw materials in the Zaskya Bakery Home Industry by using EOQ. Survey and observation with a quantitative descriptive approach are The methods used in this research. Data analysis uses the calculation formula of EOQ, total inventory cost, safety stock, and reorder point. The results showed that the application of the EOQ method in controlling raw material inventory was an emphasis on inventory costs on the Zaskya Bakery Home Industry. The Efficiency of the quantity of raw material ordering each time order, the time of re-ordering of raw materials, as well as the quantity of safety inventory can be known.